Clinical Advocacy: How Physicians Fight Back against Bureaucratic and Financial Pressures - Alexandra E Brewer; Stefan Timmermans (Journal of Health and Social Behavior, 2026)
The commercialization and corporatization of U.S. health care have intensified bureaucratic and economic constraints on clinical decision-making. Drawing on data from a 21-month ethnography of hospital-based clinicians, we introduce clinical advocacy as the often invisible work clinicians undertake to secure care that they judge medically appropriate when third parties external to the patient–provider relationship restrict medical practice. We identify four recurrent strategies of clinical advocacy: directly appealing to decision makers, altering medical records, manipulating hospital stays, and changing medical treatment. While these tactics can unlock lifesaving medical resources, they also come with negative consequences for patients in terms of medical risks and widening inequalities; for providers in terms of administrative burden, burnout, stress, and interprofessional conflict; and for the health care system in terms of inefficiencies and waste. We argue that clinical advocacy reflects a shift in institutional arrangements in which physicians increasingly function as frontline safeguards against third-party profit maximization.